2013
DOI: 10.1056/nejmoa1215340
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel with Aspirin in Acute Minor Stroke or Transient Ischemic Attack

Abstract: Among patients with TIA or minor stroke who can be treated within 24 hours after the onset of symptoms, the combination of clopidogrel and aspirin is superior to aspirin alone for reducing the risk of stroke in the first 90 days and does not increase the risk of hemorrhage. (Funded by the Ministry of Science and Technology of the People's Republic of China; CHANCE ClinicalTrials.gov number, NCT00979589.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
1,025
7
17

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 1,479 publications
(1,143 citation statements)
references
References 29 publications
26
1,025
7
17
Order By: Relevance
“…The CHANCE trial was a randomized, double‐blind, controlled trial that enrolled 5170 patients within 24 hours after onset of minor stroke (National Institutes of Health Stroke Scale [NIHSS] ≤3) or high‐risk TIA (ABCD 2 ≥4) from 114 clinical centers in China 18, 19, 20. In total, 73 (64%) of 114 participating hospitals voluntarily participated in the serum biomarker substudy in the CHANCE trial.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CHANCE trial was a randomized, double‐blind, controlled trial that enrolled 5170 patients within 24 hours after onset of minor stroke (National Institutes of Health Stroke Scale [NIHSS] ≤3) or high‐risk TIA (ABCD 2 ≥4) from 114 clinical centers in China 18, 19, 20. In total, 73 (64%) of 114 participating hospitals voluntarily participated in the serum biomarker substudy in the CHANCE trial.…”
Section: Methodsmentioning
confidence: 99%
“…The primary efficacy outcome was a new stroke (ischemic or hemorrhagic) within 90 days 18. Recurrent stroke was defined by the presence of a sudden new symptomatic neurological deficit on a background of stability or improvement after the presenting event 22.…”
Section: Methodsmentioning
confidence: 99%
“…Early and short‐term use of two agents appears to be superior to monotherapy, as suggested by observational studies (EXPRESS, SOS 1, 2), small trials (FASTER, EARLY) 24, 25, and a post hoc subgroup analysis of the PRoFESS mega‐trial 26. These findings were strengthened by the large CHANCE trial that showed that the combination of aspirin + clopidogrel was superior to aspirin alone in reducing stroke recurrence 23. Indeed, it appears in meta‐analyses that any pair of antiplatelets is superior to any single agent 27, 28.…”
Section: Introduction and Rationalementioning
confidence: 96%
“…While oral anticoagulants are established therapy after cardioembolic stroke and TIA 11, 12, 13, 14, the majority of patients with acute and chronic ischemic stroke or TIA need antiplatelets 15, 16, 17, 18, 19, 20, 21, 22, 23.…”
Section: Introduction and Rationalementioning
confidence: 99%
“…For example, GpIIb/IIIa inhibitors do not lead to an improvement in functional outcome compared to aspirin alone, perhaps because they increase the risk of intracranial haemorrhage. However, when clopidogrel and aspirin were targeted to Chinese patients with a particularly high risk of recurrent ischemic stroke, and low risk of haemorrhage – patients with recent TIA – the more intensive regime led to a net clinical benefit: fewer ischemic strokes, with no increase in intracranial haemorrhage 2. This hypothesis is of great interest in recent TIA, and being explored in different populations (Platelet Orientated Inhibition in New TIA, POINT, NCT00991029) and with more intensive antiplatelet regimes (Triple Antiplatelets for Reducing Dependence After Ischaemic Stroke, TARDIS, ISRCTN47823388).…”
Section: Introductionmentioning
confidence: 99%